IVIVC from Long Acting Olanzapine Microspheres - Susan D'Souza; Jabar A. Faraj; Stefano Giovagnoli; Patrick P. DeLuca (International Journal of Biomaterials)
In this study, four PLGA microsphere formulations of Olanzapine were characterized on the basis of their in vitro behavior at 37°C, using a dialysis based method, with the goal of obtaining an IVIVC. In vivo profiles were determined by deconvolution (Nelson-Wagner method) and using fractional AUC. The in vitro and in vivo release profiles exhibited the same rank order of drug release. Further, in vivo profiles obtained with both approaches were nearly superimposable, suggesting that fractional AUC could be used as an alternative to the Nelson-Wagner method. A comparison of drug release profiles for the four formulations revealed that the in vitro profile lagged slightly behind in vivo release, but the results were not statistically significant (P<0.0001). Using the four formulations that exhibited different release rates, a Level A IVIVC was established using the deconvolution and fractional AUC approaches. A nearly 1 : 1 correlation (R2>0.96) between in vitro release and in vivo measurements confirmed the excellent relationship between in vitro drug release and the amount of drug absorbed in vivo. The results of this study suggest that proper selection of an in vitro method will greatly aid in establishing a Level A IVIVC for long acting injectables.